1992
DOI: 10.1002/prsb.720110412
|View full text |Cite
|
Sign up to set email alerts
|

Process safety testing program for reducing risks associated with large scale chemical manufacturing operations

Abstract: The reduction of risks associated with chemical processing operations is essential for the safe operation of chemical plants. The reduction of these risks is accomplished through a comprehensive process safety management program. Key elements of this program include Hazard and Operability Studies, Emergency Relief Venting, Process Automation, Management of Change Control Procedures, Process Specific Training, and so forth. Central to many of these elements is a thorough, in‐depth understanding of the reactive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Fisher (1990) assessed available data for Hanford wastes with respect to the Kyshtym event and other available reactivity data and concluded that the temperatures of wastes stored in Hanford's USTs are well below those required for initiation of reactions between sodium acetate and sodium nitrate and/or nitrite. Chemical reactivity hazards are controlled by several thermochemical and physical factors such as the amount of energy produced by a reaction, the rate at which energy is produced, and the rate at which heat is dissipated from the system (Sharkey et al 1992). For theorganic-bearing waste system, factors that will determine the energy produced include fuel concentration, the chemical nature of the organic fuel, oxidant concentration, the nature of the oxidant@), and the chemical reaction mechanism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fisher (1990) assessed available data for Hanford wastes with respect to the Kyshtym event and other available reactivity data and concluded that the temperatures of wastes stored in Hanford's USTs are well below those required for initiation of reactions between sodium acetate and sodium nitrate and/or nitrite. Chemical reactivity hazards are controlled by several thermochemical and physical factors such as the amount of energy produced by a reaction, the rate at which energy is produced, and the rate at which heat is dissipated from the system (Sharkey et al 1992). For theorganic-bearing waste system, factors that will determine the energy produced include fuel concentration, the chemical nature of the organic fuel, oxidant concentration, the nature of the oxidant@), and the chemical reaction mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…This report presents the results of our initial chemical reactivity and energetics studies. These studies have focused on developing the thermal sensitivity,.energetics, and kinetics information necessary (Sharkey et. al.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical reactivity hazards are controlled by several thermochemical and physical factors, such as the amount of energy produced by a reaction, the rate at which energy is produced, and the rate at which heat is dissipated from the system (Sharkey et al 1992). For the organic-bearing wastes, factors that will determine the energy produced include fuel concentration, the chemical nature of the organic fuel, oxidant concentration, the nature of the oxidant(s), and the chemical reaction mechanism.…”
Section: Factors Controlling Chemical Reactivity Hazardsmentioning
confidence: 99%
“…Adiabatic calorimetry, such as ARC, is one of the principal methodologies used by the chemical industry to evaluate chemical hazards (Sharkey et al 1992;West 1993). Adiabatic calorimetry can 1) be used to provide more accurate onset temperatures than DSC or DTA (Fenlon 1984), 2) measure reaction enthalpy or energy resulting from an exothermic reaction, and 3) provide thennokinetic parameters.…”
Section: Accelerating Rate Calorimetermentioning
confidence: 99%
“…Differential scanning calorimetry and DTA are recommended techniques for screening a chemical system for exothermic behavior and for providing preliminary information on reaction onset temperature and heat of reaction (Sharkey et al 1992;West 1993;Hoppe 1992). The two instruments have similar applications since both observe heat production or absorption the temperature of a small (2 to 100 mg) sample increased at a known, controlled, and constant rate.…”
Section: Differential Scanning Calorimetry and Differential Thermal Amentioning
confidence: 99%